Method for filling gaps between MiniLED or MicroLED lamp beads and simultaneously attaching polarizer or protective film
By using SCA optical glue and vacuum hard-to-hard bonding technology, filling the lamp bead gaps of MiniLED or MicroLED display screens and applying polarizers or protective sheets, the problems of complex process, poor bonding quality and high product scrapping rate in the prior art are solved, and an efficient and low-cost production process is achieved.
Patent Information
- Application Number
- CN202210162310.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-02-22
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2042-02-22
AI Technical Summary
The filling glue process of existing MiniLED or MicroLED displays is complex, and the leveling effect after curing is poor, which affects the quality of the fitting and is difficult to rework after curing, resulting in high product scrapping rate and increased cost.
SCA optical adhesive is used to fill the gaps in the lamp beads of MiniLED or MicroLED through combination and vacuum hard bonding, and at the same time, it is applied to the polarizer or protective sheet. The method includes die-cut SCA optical glue, soft-to-hard bonding, vacuum hard-to-hard bonding, and hot melt filling.
It improves production efficiency, reduces operation difficulty and poor process, reduces product scrapping, and improves product resistance and service life.
Smart Images

Figure CN114709322B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of MiniLED or MicroLED, and in particular to a method of filling the gaps between MiniLED or MicroLED lamp beads with a hot-melt optical adhesive film and simultaneously attaching a polarizer or a protective film. Background Art
[0002] MiniLED or Micro LED display technology is an improvement over LED display, which is to make the LED display's lamp beads smaller and denser to form light-emitting pixel units, and assemble them on the drive panel to form a high-density LED array display technology. Due to the characteristics of small chip size, high integration and self-luminescence, MiniLED and Micro LED have greater advantages in brightness, resolution, contrast, energy consumption, service life, response speed and thermal stability compared with LCD and OLED in terms of display.
[0003] MiniLED and Micro LED are easily affected by the external environment because their lamp beads are exposed to the outside, which will also reduce the service life of MiniLED and Micro LED displays. The existing solution generally uses a process called glue filling to fill the gaps between the lamp beads of MiniLED and MicroLED, and then after the glue is cured and dried, a layer of polarizer or protective film is attached to its surface. Thus, the final MiniLED and Micro LED display is formed. The problems with this method are: 1. The process is relatively complicated, resulting in low production efficiency; 2. The glue has poor leveling effect after curing, resulting in an uneven surface, affecting the subsequent bonding and resulting in a low bonding yield; 3. Because glue curing is used, it is impossible or difficult to rework after curing, resulting in a high product scrap rate and increased costs.
[0004] Therefore, it is of great practical significance to develop a new process for filling the gaps between MiniLED and MicroLED lamp beads and laminating polarizers or protective films at the same time, which can overcome the above-mentioned technical defects. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a new method for filling the gaps of MiniLED or MicroLED lamp beads and laminating a polarizer or protective film at the same time. The principle is to use SCA optical glue purchased on the market, through combination and vacuum hard-to-hard lamination, to achieve filling the gaps of MiniLED or MicroLED lamp beads and laminating a polarizer or protective film at the same time.
[0006] The present invention provides a novel method for filling the gaps of MiniLED or MicroLED lamp beads and simultaneously attaching a polarizer or a protective film, comprising the following steps:
[0007] 1) Confirm the thickness of the lamp beads of the MiniLED or MicroLED display screen, and select SCA optical glue with a thickness matching the thickness of the lamp beads; the thickness of the SCA optical glue is 100-150 μm higher than the thickness of the lamp beads;
[0008] 2) die-cutting the SCA optical adhesive;
[0009] 3) Remove the light release film from the die-cut SCA optical adhesive and perform soft-to-hard bonding with the polarizer or protective film;
[0010] 4) Place the MiniLED or MicroLED display screen on the alignment jig, the inner groove height of the jig is 0.2-0.3mm lower than the final product height; this design can prevent glue overflow, and a layer of release agent or silicone oil needs to be applied after 5-10 operations in the inner groove of the jig;
[0011] 5) Remove the heavy release film of the SCA optical adhesive from the sample with the polarizer or protective film attached obtained in step 3), and attach and fix it on the MiniLED or MicroLED lamp bead to complete the assembly process;
[0012] 6) placing a layer of 1-2 mm thick tempered glass on the top of the polarizer or protective film after the combination process of step 5) (the side not bonded with the SCA optical adhesive);
[0013] 7) placing the sample obtained in step 6) on the working platform of the SCA hard-to-hard laminating machine, and sending the sample into a sealed vacuum and hard-to-hard laminating chamber for evacuation; then using a hot constant temperature heating plate in the SCA hard-to-hard laminating machine to press the sample under vacuum, so that the colloid is heated, melted and softened, and fills the gaps between the lamp beads;
[0014] 8) After the hard-to-hard bonding is completed, remove the tempered glass placed on the polarizer or protective film, and then remove the product from the fixture;
[0015] 9) After the product has cooled, conduct appearance and function inspections. Defective products will be returned for disassembly (rework) and good products will continue to the next process. The inspection standards are as follows:
[0016] Table 1 Appearance inspection standards
[0017]
[0018]
[0019] Table 2 Functional test - inspection standards after the display is lit
[0020]
[0021] 10) Place the good product with the polarizer or protective film facing up on the tray and bake it for curing. After curing, wait for the product to cool down and then take it out.
[0022] 11) After taking out the product, check whether there is any glue overflow on the edge. If there is any glue overflow, use a blade coated with release agent to clean the glue.
[0023] The method further comprises the step of cutting the edges and corners after curing to remove excess glue and edges and corners. This process can be completed by CNC (numerical control milling machine) or manual cutting.
[0024] The method further comprises: after step 8) and before step 9), the sample is removed from the alignment jig; or, after curing is completed in step 10), the sample is removed from the alignment jig.
[0025] In step 1) of the above method, the SCA optical adhesive may be specifically the SCA optical adhesive of Shenzhen Gaoren Electronic New Materials Co., Ltd., model SCA-T, with a thickness of 300 μm.
[0026] The thickness of the adhesive material must be 100-150μm higher than the lamp beads. The verification data is as follows;
[0027] Rubber material model thickness Lamp height result SCA-T 200μm 200μm Fit the entire surface with large bubbles SCA-T 250μm 200μm There are bubbles in the gaps between the lamp beads SCA-T 300μm 200μm No bubbles after bonding
[0028] In step 3) of the above method, the bonding method may be performed by using a soft-to-hard flipping machine, or by using a bonding jig for manual bonding.
[0029] In step 4) of the above method, when using a laminating jig, a layer of release agent or silicone oil needs to be applied to the edge of the inner groove of the jig after every 5-10 operations. The following is the verification data;
[0030] Number of operations (times) Glue condition on the edge of the fixture determination 1-5 No adhesive OK 5-10 No adhesive OK 10-15 A small amount of glue on the edge NG 15-20 Lots of glue on the edges NG
[0031] In step 6) of the above method, the thickness of the tempered glass is 1-2 mm.
[0032] In step 7) of the above method, the vacuum value of the vacuum pumping is ≥-98kpa, and the vacuum pumping time can be ≥30s. The temperature of the hard-to-hard bonding is set at 80-85°C, the pressure is set at 0.3-0.5Mpa, and the time is 180-240s; the specific conditions can be: the temperature is set at 85°C, the pressure is set at 0.45Mpa, and the time is 200s.
[0033] The working principle of step 7) of the above method is: first, the air between the lamp beads and the glue layer and the polarizer or protective film and the glue layer in the sample is extracted, and then the SCA optical glue is completely melted and its fluidity is increased by transmitting the temperature through the constant temperature heating plate, while applying pressure to squeeze the optical glue into the gap of the lamp beads (the air in the squeezed gap is extracted again), so that it can completely fill the gap of the lamp beads. In this process, the surface of the polarizer or protective film is evenly stressed by the protection of tempered glass, and it is not easy to form uneven marks, so as to achieve the effect of fitting the polarizer or protective film.
[0034] In step 8) of the above method, during the glue removal, a silicone oil release agent needs to be applied on the blade.
[0035] In step 10) of the above method, the curing parameters are the same as the curing parameters of the SCA optical adhesive.
[0036] When the SCA optical adhesive used is the SCA optical adhesive of Shenzhen Gaoren Electronic New Materials Co., Ltd., the model is SCA-T, the thickness is 300μm, and the curing parameters can be: temperature 120℃, time 60min.
[0037]
[0038]
[0039] By comparison, it was found that only the thermosetting SCA-T optical adhesive can meet such process conditions.
[0040] Compared with the prior art, the above technical solution has the following advantages: because SCA optical adhesive is used as the bonding adhesive, it can maximize the production efficiency, reduce the difficulty of operation, and reduce the number of process defects. At the same time, due to the characteristics of this adhesive film, its initial adhesion is low before curing (as shown in Table 3), making it easy to disassemble and minimize product scrapping, thereby improving the overall cost of the product. At the same time, after curing (as shown in Table 4), it has strong adhesion, so that the product will not have problems such as debonding or bubble rebound during later use, which can improve the reliability of the product.
[0041] The SCA optical adhesives measured in Tables 3 and 4 are all SCA optical adhesives produced by Shenzhen Gaoren Electronic New Materials Co., Ltd., with a product model of SCA-T and a thickness of 300 μm.
[0042] Table 3: Test data of peeling force of uncured SCA optical adhesive on glass
[0043]
[0044] Table 4: Test data of peeling force of SCA optical adhesive on glass after curing
[0045] BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 A flow chart of a vacuum hard-to-hard bonding process for filling the gaps between MiniLED or MicroLED lamp beads and bonding a polarizer or a protective film at the same time provided by the present invention.
[0047] Figure 2 This is a schematic diagram of the structure of the product prepared by the present invention; wherein, 1: PCB board, 2: LED lamp beads; 3: SCA optical glue; 4: polarizer\protective film. DETAILED DESCRIPTION
[0048] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods described are conventional methods unless otherwise specified. The raw materials described can be obtained from public commercial channels unless otherwise specified.
[0049] The SCA optical adhesive used in the following examples was purchased from Shenzhen Gaoren Electronic New Materials Co., Ltd., product model SCA-T, thickness 300 μm. The SCA hard-to-hard bonding machine was purchased from Shenzhen Yongquan Automation Equipment Co., Ltd., product model YQ-E0900 (32 inches).
[0050] Embodiment 1,
[0051] 1. Confirm the thickness of the lamp beads of the MiniLED or MicroLED display (200μm), and select SCA optical glue (product model SCA-T) that matches the thickness of the lamp beads, with a thickness of 300μm.
[0052] 2. After confirming the thickness of the SCA optical adhesive, die-cut the optical adhesive.
[0053] 3. Remove the light release film from the die-cut SCA optical adhesive and perform soft-to-hard bonding with the polarizer or protective film; this bonding can be done using a soft-to-hard flip machine.
[0054] 4. Place the MiniLED or MicroLED display screen on the alignment jig. The inner groove height of the jig is 0.2-0.3mm lower than the final product height; at the same time, a layer of release agent or silicone oil needs to be applied after 5-10 operations in the inner groove of the jig;
[0055] 5. Tear off the heavy release film of the SCA optical adhesive of the sample with the polarizer or protective film attached in step 3), and attach and fix it on the MiniLED or MicroLED lamp bead to complete the assembly process.
[0056] 6. After completing the combination process in step 5), a layer of tempered glass with a thickness of 1 mm is placed on top of the polarizer or protective film of the MiniLED or MicroLED display.
[0057] 7. Place the sample completed in step 6 on the working platform of the SCA hard-to-hard laminating machine and send the sample into the vacuum and hard-to-hard laminating chamber.
[0058] 8. The fabricated samples were evacuated in a sealed vacuum and hard-to-hard bonding chamber, with a vacuum value of -96 kPa and a evacuation time of 30 seconds.
[0059] 9. When the vacuum time is reached, use the hot constant temperature heating plate in the equipment to perform hard-to-hard bonding on the sample under vacuum, so that the colloid of SCA optical glue is melted and softened by heat, filling the gaps between the lamp beads. The temperature is set at 85°C, the pressure is set at 0.45Mpa, and the time is 200s. The hard-to-hard bonding is completed.
[0060] 10. After the hard-to-hard bonding is completed, remove the tempered glass placed on the polarizer or protective film, take out the product, and remove the sample from the alignment fixture. Use a blade (with silicone release agent) to clean the glue overflow on the edge. (The step of removing the sample from the alignment fixture can also be completed after the subsequent curing process)
[0061] 11. After the edge of the product is cleaned, the function and appearance are inspected (see Table 1 and Table 2 above), and defective products are returned for disassembly (rework). Good products continue to the next process.
[0062] 12. Place the good polarizer or protective film on the tray with the surface facing up and bake it for curing. The curing parameters for the sample preparation are: temperature 120℃, time 60min.
[0063] 13. After curing, cut the edges and corners to remove excess glue and corners. This process can be completed by CNC (CNC milling machine) or manual cutting.
[0064] The performance of the products prepared above was tested. The yield of the finished products is shown in Table 5 below, and the signal resistance test (environmental test) is shown in Table 6 below.
[0065] Table 5
[0066]
[0067] Table 6
[0068] Test items condition Test Standards Number of inputs Number of good products determination High temperature and humidity 85℃-85%RH、500h GB / T 32368-2015 5 5 OK UV Aging QUV, 500h GB / T 16422.3-2014 5 5 OK Low temperature storage -40℃、500h GB / T 2423.1-2008 5 5 OK High temperature storage 80℃、500h GB / T 2423.2-2008 5 5 OK Hot and cold shock (80℃ / 30min, -40℃ / 30min)500h GB / T 2423.22-2002 5 5 OK
[0069] Comparative Example 1: Use SCA-TC optical adhesive to fill the gaps between MiniLED or MicroLED lamp beads while attaching a polarizer or protective film
[0070] The method is basically the same as Example 1, except that the SCA optical adhesive (model SCA-T) in Example 1 is replaced by SCA-TC optical adhesive (purchased from Shenzhen Gaoren Electronic New Materials Co., Ltd.; model: SCA-TC, thickness 300 μm, curing parameters: light source type LED, band: 365 nm, UV light volume: 5000-6000 mJ / cm 2 . )
[0071] In step 11 of Example 1, the performance of hot melt adhesive filling of the two is compared, see Table 7.
[0072] Table 7 Comparison of bonding yield between SCA-T optical adhesive and SCA-TC optical adhesive
[0073] Rubber Number of inputs Poor air bubbles Yield SCA-T 10 0 100% SCA-TC 10 10 0%
[0074] Through hard-to-hard bonding verification, it was found that SCA-T optical glue has better fluidity and is more conducive to filling the gaps under the lamp beads without generating bubbles. However, SCA-TC optical glue is UV-cured and has poor temperature resistance. At a temperature where the colloid does not fog, its fluidity is poor, which is not conducive to filling the gaps under the lamp beads and easily generates bubbles between the gaps between the lamp beads.
[0075] Comparative Example 2: Using EVA hot melt adhesive to fill the gaps between MiniLED or MicroLED lamp beads while attaching a polarizer or protective film
[0076] The same as Example 1, except that the SCA optical adhesive in Example 1 is replaced with EVA hot melt adhesive (purchased from Gaoren; model: ASQ8, specification 380um; curing parameters: 130°C, 60min)
[0077] In step 11 of Example 1, the performance of hot melt adhesive filling of the two was compared, see Table 8.
[0078] Table 8 Comparison of bonding yield between SCA optical adhesive and EVA hot melt adhesive
[0079]
[0080]
[0081] Through hard-to-hard bonding verification, it was found that SCA optical glue has better fluidity and is more conducive to filling the gap under the lamp beads without generating bubbles. However, EVA hot melt glue has poor fluidity and is not conducive to filling the gap under the lamp beads, and is prone to generating bubbles at the edge of the lamp beads.
Claims
1. A method for filling the gaps of MiniLED or MicroLED lamp beads and simultaneously attaching a polarizer or a protective film, comprising the following steps: 1) Confirm the thickness of the lamp beads of the MiniLED or MicroLED display screen, and select SCA optical glue with matching thickness according to the thickness of the lamp beads; the thickness of the SCA optical glue is 50-100μm higher than the thickness of the lamp beads; 2) die-cutting the SCA optical adhesive; 3) Remove the light release film from the die-cut SCA optical adhesive and laminate it with the polarizer or protective film; 4) Place the MiniLED or MicroLED display on the alignment fixture; 5) Remove the heavy release film of the SCA optical adhesive from the sample with the polarizer or protective film attached obtained in step 3) and attach and fix it to the MiniLED or MicroLED lamp bead to complete the assembly process; 6) placing a layer of tempered glass on top of the polarizer or protective film after the combination process of step 5); 7) placing the sample obtained in step 6) on the working platform of the SCA hard-to-hard laminating machine, and sending the sample into a sealed vacuum and hard-to-hard laminating chamber for evacuation; then performing hard-to-hard lamination of the sample under vacuum using a hot constant temperature heating plate in the SCA hard-to-hard laminating machine; 8) After the hard-to-hard bonding is completed, remove the tempered glass placed on the polarizer or protective film, and then take out the product and use a blade to clean the glue overflow on the edge; 9) After the edge of the product is cleaned, the appearance and function are inspected, defective products are returned for disassembly, and good products continue to the next process; 10) Place the good polarizer or protective film surface facing up on the tray and bake it for curing.
2. The method according to claim 1, characterized in that: In the step 1), the SCA optical adhesive has a thickness of 300 μm, and its curing parameters are: temperature 120° C., and time 60 min.
3. The method according to claim 1 or 2, characterized in that: In the step 3), the laminating method is to use a soft-to-hard flipping machine for laminating, or to use a laminating jig for manual laminating.
4. The method according to claim 1 or 2, characterized in that: In the step 4), the height of the inner groove of the jig is 0.1-0.2 mm lower than the height of the final product; and a layer of release agent or silicone oil needs to be applied after the inner groove of the jig has been operated 5-10 times.
5. The method according to claim 1 or 2, characterized in that: In the step 6), the thickness of the tempered glass is 1-2 mm.
6. The method according to claim 1 or 2, characterized in that: In the step 7), the vacuum value of the vacuum pumping is -96-98 kPa, and the vacuum pumping time is 10-50 s.
7. The method according to claim 1 or 2, characterized in that: In the step 7), the temperature of the hard-to-hard bonding is set at 75-85° C., the pressure is set at 0.05-0.45 MPa, and the time is 90-240 seconds.
8. The method according to claim 1 or 2, characterized in that: The method further comprises: after step 8) and before step 9), the sample is removed from the alignment jig; or after curing is completed in step 10), the sample is removed from the alignment jig.
9. The method according to claim 1 or 2, characterized in that: The method further comprises: after step 10) curing is completed, the edges and corners are cut to remove excess glue and edges and corners.
Citation Information
Patent Citations
LED-based two-sided-grating three-dimensional display device and manufacturing method thereof
CN102608768A
Method for Removing Screen Coating Film
US20170299258A1